(im Druck) Zur generationstheoretischen Analyse medienbiografischer Topoi. Eine medienpädagogische Perspektive - Dehmel, Lukas; Meister, Dorothee M. (Medien, Biografien und Generationen)

A mixed‐methods study of the quality of parental support during adolescents' information‐related Internet use as a co‐construction process - Kurock, Ricarda; Teichert, Jeannine; Meister, Dorothee M.; Gerhardts, Lara; Buhl, Heike M.; Bonanati, Sabrina (Journal of Adolescence)
Abstract Introduction In Europe, most Internet searches for school‐related tasks are situated at home, where parents can support adolescents. Although the frequency (quantity) of parental support has already been analyzed, a research gap exists concerning the quality of parental support in adolescents' information‐related Internet use. The quality of parental support in the field of homework involvement is known to be a predictor of adolescents' learning motivation and academic achievement, often discussed with regard to self‐determination theory (SDT) in terms of autonomy support, structure, emotional support, and control. These categories were adapted in this study to analyze parents' support in adolescents' Internet searching activities. Methods Using a mixed‐methods approach, we combined quantitative questionnaires and qualitative observations to analyze joint information‐related Internet uses. Therefore, 243 parent–adolescent dyads were surveyed and six parent–adolescent dyads were observed by videography in 2019/2020 in Germany. The adolescents were 11 years old, on average. Results The parents rated all qualities higher than the adolescents. Emotional support was rated highest by both groups, whereas structure was rated lowest. Adolescents' and parents' view on parental support differ. The qualitative study revealed parents' often interfering behavior, whereas emotional support was low. Further, the active role of adolescents was highlighted in both quantitative and qualitative data. Conclusions By combining quantitative and qualitative approaches, we demonstrated a fruitful application of SDT in analyzing the quality of parental support during adolescents' Internet searches at home and shed light on the co‐construction of joint Internet searches.
Keywords: Psychiatry and Mental health; Developmental and Educational Psychology; Social Psychology; Pediatrics; Perinatology and Child Health

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister, Dorothee M. (MedienPädagogik)

Die Entgrenzung von Kommunikationskulturen in Lehrpersonenkollegien. Reflexion einer unbeabsichtigten Begleiterscheinung der Arbeit mit Tablets. - Dehmel, Lukas; Meister, Dorothee; Gerhardts, Lara (Zeitschrift MedienPädagogik)

Aushandlungen von Inklusion und Exklusion im Kontext der (nicht-)Verfügbarkeit mobiler Medien. Ein rekonstruktiver Blick auf die Mediatisierung berufsschulischer Möglichkeitsräume. - Dehmel, Lukas; Meister, Dorothee (Jahrbuch Medienpädagogik 20. Inklusive Medienbildung in einer mediatisierten Welt. Medienpädagogische Perspektiven auf ein interprofessionelles Forschungsfeld.)